Bond strength to dentin of low-shrinkage composite resin restorations after thermocycling and mechanical loading - Chiba, Erika Kiyoko; Briso, André Luiz Fraga; de Alexandre, Rodrigo Sversut; Moda, Mariana Dias; Dos Santos, Paulo Henrique; Fagundes, Ticiane Cestari (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Objective: This study evaluated the in vitro bond strength of Class I restorations to dentin, using four restorative systems. Materials and Methods: Ninety-six molars were used, and a Class I cavity was prepared on the occlusal surface. Next, tooth were divided into 4 groups (n=24), Single Bond Universal + Filtek Z350 XT (SFZ); Single Bond Universal + Filtek Bulk Fill (SFB); AdheSE + Tetric N-Ceram (ATC) and AdheSE + Tetric N-Ceram Bulk Fill (ATB).Thus, the teeth were divided into 3 subgroups (n = 8): 1) storage in water for 24h (control); 2) submitted to thermocycling; 3) mechanical loading. After challenges, teeth were cut into beams 0.8mm², being 3 to 4 sticks per tooth. Then, the specimens were submitted to microtensile testing (μTBS). The data were submitted to Kruskal Wallis and Dunn tests for multiple comparisons, with a significance level of 5%. Results: No significant differences were observed between the restorative systems after thermal cycling challenge (p> 0.05). However, the SFZ group presented the highest μTBS values, with a statistical difference when compared to the ATC, SFB and ATB groups after mechanical loading (p> 0.05). Conclusion: The dentin bond strength of low-shrinkage composite resin restorations was negatively influenced by mechanical loading in class I cavities. Descriptors: Dental Materials; Permanent Teeth; Resin Composite; Restoration; Substrate Cycling. References Bedran-Russo A, Leme-Kraus AA, Vidal CMP, Teixeira EC. An overview of dental adhesive systems and the dynamic tooth-adhesive interface. Dent Clin N Am. 2017; 61:713-31. Rosatto CM, Bicalho AA, Veríssimo C, Bragança GF, Rodrigues MP, Tantbirojn D, et al. Mechanical properties, shrinkage stress, cuspal strain and fracture resistance of molars restored with bulk-fill composites and incremental filling technique. J Dent. 2015;43:1519-28. Ilie N, Bucuta S, Draenert M. Bulk-fill resin-based composites: an in vitro assessment of their mechanical performance. Oper Dent. 2013;38:18-25. Caixeta RV, Guiraldo RD, Kaneshima EN, Barbosa AS, Picolotto CP, Lima AE, et al. Push-out bond strength of restorations with bulk-fill, flow, and conventional resin composites. ScientificWorldJournal 2015; 2015:452976. Amaral FL, Colucci V, Palma-Dibb RG, Corona SA. Assessment of in vitro methods used to promote adhesive interface degradation: a critical review. J Esthet Restor Dent. 2007;19:340-53. Daneshkazemi A, Davari A, Akbari MJ, Davoudi A, Badrian H. Effects of thermal and mechanical load cycling on the dentin microtensile bond strength of Single Bond-2. J Int Oral Health 2015;7:9-13. Poptani B, Gohil KS, Ganjiwale J, Shukla M.Microtensile dentin bond strength of fifth with five seventh-generation dentin-bonding agents after thermocycling: An in vitro study. Contemp Clin Dent. 2012;3(Suppl 2):S167-71. Heintze SD, Monreal D, Peschke A. Marginal quality of Class II composite restorations placed in bulk compared to an incremental technique: Evaluation with SEM and Stereomicroscope. J Adhes Dent. 2015;17:147-54. Soares CJ, Pizi EC, Fonseca RB, Martins LR. Influence of root embedment material and periodontal ligament simulation on fracture resistance tests. Braz Oral Res. 2005;19:11-6. Aguiar TR, André CB, Correr-Sobrinho L, Arrais CA, Ambrosano GM, Giannini M. Effect of storage times and mechanical load cycling on dentin bond strength of conventional and self-adhesive resin luting cements. J Prosthet Dent. 2014;111:404-10. Assunção WG, Jorge JR, Dos Santos PH, Barão VA, Gomes EA, Delben JA. The effect of mechanical cycling and different misfit levels on Vicker’s microhardness of retention screws for single implant-supported prostheses J Prosthodont. 2011;20:523-27. De Munck J, Luehrs AK, Poitevin A, Van Ende A, Van Meerbeek B. Fracture toughness versus micro-tensile bond strength testing of adhesive-dentin interfaces. Dent Mater. 2013;29:635-44. Armstrong S, Breschi L, Özcan M, Pfefferkorn F, Ferrari M, Van Meerbeek B. Academy of Dental Materials guidance on in vitro testing of dental composite bonding effectiveness to dentin/enamel using micro-tensile bond strength (μTBS) approach. Dent Mater. 2017;33:133-43. Tjäderhane L, Nascimento FD, Breschi L, Mazzoni A, Tersariol IL, Geraldeli S et al. Strategies to prevent hydrolytic degradation of the hybrid layer- A review. Dent Mater. 2013; 29:999-11. Taneja S, Kumar P, Kumar A. Comparative evaluation of the microtensile bond strength of bulk fill and low shrinkage composite for different depths of Class II cavities with the cervical margin in cementum: An in vitro study. J Conserv Dent. 2016;19:532-35. Campos EA, Ardu S, Lefever D, Jassé FF, Bortolotto T, Krejci iI. Marginal adaptation of class II cavities restored with bulk-fill composites. J Dent. 2014;42;575-81. Mandava J, Vegesna DP, Ravi R, Boddeda MR, Uppalapati LV, Ghazanfaruddin MD. Microtensile bond strength of bulk-fill restorative composites to dentin. J Clin Exp Dent. 2017;9:e1023-28. Costa T, Rezende M, Sakamoto A, Bittencourt B, Dalzochio P, Loguercio AD, et al. Influence of adhesive type and placement technique on postoperative sensitivity in posterior composite restorations. Oper Dent. 2017;42:143-54. Jayaseel A, Niranjan N, Pamidi H, Suryakanth MB. Comparative evaluation of shear bond strength of universal dental adhesives - An in vitro study. J Clin Exp Dent. 20171;9:e892-e96. Silame FDJ, Geraldeli GP, Sinhoreti MAC, Pires-de-Souza FCP, Roulet JF, Geraldeli S. Dentin µTBS and hardness of bulk-fill and conventional composites placed in a box-shaped cavity preparation. J Adhes Dent. 2017;19:395-400. Han SH, Park SH. Comparison of internal adaptation in class II bulk-fill composite restorations using micro-CT. Oper Dent. 2017;42:203-14. Al-Harbi F, Kaisarly D, Michna A, ArRejaie A, Bader D, El Gezawi M. Cervical interfacial bonding effectiveness of class II bulk versus incremental fill resin composite restorations Oper Dent. 2015;40:622-35. Amaral FL, Colucci V, Palma-Dibb RG, Corona SA. Assessment of in vitro methods used to promote adhesive interface degradation: a critical review J Esthet Restor Dent. 2007; 19:340-53. Lezaja Zebic M, Dzeletovic B, Miletic V. Microtensile bond strength of universal adhesives to flat versus Class I cavity dentin with pulpal pressure simulation J Esthet Restor Dent. 2018;30:240-48. Yazici AR, Antonson SA, Kutuk ZB, Ergin E. Thirty-six-month clinical comparison of bulk fill and nanofill composite restorations. Oper Dent. 2017;42:478-85.